PENGARUH SISTEM PERPAJAKAN, PENGETAHUAN PERPAJAKAN, TARIF PAJAK DAN SANKSI PERPAJAKAN TERHADAP PERILAKU PENGGELAPAN PAJAK PADA WAJIB PAJAK DI KANTOR PELAYANAN PAJAK (KPP) PRATAMA SERPONG - Muhammad Rizal Saragih; Rusdi Rusdi (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to analyze the behavior of tax evasion by taxpayers in the Serpong Tax Office. In the test, it involves the variables of the taxation system, knowledge of taxation, tariffs and tax sanctions. This research is a survey research, with a quantitative approach. In the process of statistical analysis, multiple linear regression techniques are used. The sampling technique was carried out incidentally to the total population of 119.925. The results of the study reveal that the tax system has loopholes that can be exploited as an effort to commit tax evasion. Likewise with tax knowledge, the better the knowledge of a taxpayer, then he will know measurable actions that can deceive the tax system. High tax rates encourage people to do tax avoidance. However, tax sanctions did not have a positive effect on reducing tax evasion. This finding confirms that the tax system, knowledge, and tax rates can trigger the occurrence of tax evasion. So it is necessary to strengthen the tax system.